Penanaman Mangrove Sebagai Upaya Pencegahan Abrasi Di Pesisir Pantai Kampung Bunsur Kecamatan Sungai Apit - Rosdiansyah Rosdiansyah; Royando Cibro; Amrizal Amrizal; Fikryah Athirah; Nurul Intan; Elika Maharani; Trivira Wulansuci; Riskita Fitria; Sagita Lestari Putri Lumban Siantar; Christina Br. Damanik (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The coastal area of Bunsur Village has a high biodiversity, but it is facing pressure due to high human activities in the surrounding waters. One of the programs carried out by the 2021 University of Riau's Community Service Learning (Kuliah Kerja Nyata) students in Bunsur Village is the planting of mangroves. The activity involves observation and education methods. The mangrove planting activity is conducted in two phases, namely preparation and implementation. The preparation phase includes field surveys and the collection of mangrove seedlings. The activity took place on July 31, 2023, involving University of Riau KKN students, the Village Head of Bunsur, village officials, neighborhood and community leaders, the Mangrove Community of Bunsur Village, the Sungai Apit police officer (Bhabinkamtibmas), elementary school teachers, youth groups from Bunsur Village, as well as the Women Farmers Group of Bunsur Village, and several residents of Bunsur Village. A total of 50 mangrove seedlings were planted, obtained through the support of the Mangrove Community of Bunsur Village Chairperson. The objective of this activity was to raise awareness among the community regarding environmental cleanliness, especially along the coastal areas. The results obtained from this activity include the formation of a new mangrove community along the coastal area, as well as a cleaner and better-organized coastline.